The Green Berets - Wayne, Joh; Barrett, James Lee; Rozla, Miklos; Hutton, Jim 1934-1979; Ray, Aldo; Janssen, David; St. Jacques, Raymond 1930-; Cabot, Bruce 1904-1972; Soo, Jack 1917-1979; Takei, George 1937-; Wayne, Patrick 1939-; Askew, Luke 1932-2012; et al. (John Wayne collection)
John Wayne leads his Special Forces troops against a deadly and determined enemy. The film combines rugged action with spectacular special effects